Electricity, national identity and regeneration in Spain around 1900. - Pérez-Zapico, Daniel (Journal of Iberian & Latin American Studies, 2023)
This article analyses how electricity and electrical technologies were used to generate a whole series of narratives about national regeneration in a context of national (and imperial) decline. It will follow the debates that the advent of the "electrical era" triggered among a group of Spanish engineers that in 1902 published the book La ciencia y la industria eléctrica en España al subir al trono S.M. el Rey Don Alfonso XIII. The publication acted as a memorandum addressed to the young monarch aimed at encouraging the promising applications of electricity in Spain. As members of an international community, engineers embraced the alleged universal promises of electricity but adapted them to Spain's local conditions. Accordingly, through the pages of the book they used technologies of electrification and electricity as cultural resources to refashion national identity and establish the foundations of a new modernity. By analysing how Spanish engineers conceived the relationship between energy and the future of the nation, this article aims at enriching the historiography of Spanish nationalisms through the lenses of the history of technology (particularly, histories of techno-nationalism) and cultural histories of electricity and energies.